Metabolic and Nutritional Outcomes After Sleeve Gastrostomy and Gastric Bypass in Adolescents: A Cohort Study with 1-Year Follow-Up - Zolfaghari, Faraneh; Barzin, Maryam; Mahdavi, Maryam; Khalaj, Alireza; Asghari, Golaleh (Hormone and Metabolic Research, 2025)
We conducted this study to compare the anthropometric and metabolic outcomes and nutritional status, after sleeve gastrostomy (SG) and gastric bypass (GB) in adolescents with severe obesity. We selected 219 adolescents with severe obesity (Body Mass Index>99th percentile or 95th≤BMI<99th percentile) among the participants of Tehran Obesity Treatment Study and assessed them for anthropometric and metabolic outcomes and nutritional status at baseline and during 1 year follow up after the surgery. Out of the total, 182 participants were in the SG group and 37 were in the GB group. BMI was lower in SG patients compared to GB group (38.5±4.8 kg/m 2 vs. 36.1±4.0 kg/m 2, p-value<0.05), 3 months after surgery. Metabolic profiles such as aspartate transaminase and alanine transaminase were lower in SG group compared to GB after 6 months of follow up, while high-density lipoprotein was higher in SG patients compered to GB patients (41.6±8.4 mg/dl vs. 48.0±9.2 mg/dl, p-value<0.05). After one year, total cholesterol and low-density lipoprotein were higher in adolescents who underwent SG compared to those in GB group. There was no significant difference in micronutrient status between SG and GB groups. It seems that SG in adolescents with obesity and fatty liver disease, is more appropriate but GB may be preferred in patients with a history of lipid profile abnormalities. More studies are needed to draw conclusions about nutritional status and long-term outcomes after surgery.
Keywords: bariatric surgery; gastric bypass; sleeve gastrostomy; adolescents; obesity